Intercalation of Bi nanoparticles into graphite results in an ultra-fast and ultra-stable anode material for sodium-ion batteries. Issue 5 (6th April 2018) - Chen, Ji; Fan, Xiulin; Ji, Xiao; Gao, Tao; Hou, Singyuk; Zhou, Xiuquan; Wang, Luning; Wang, Fei; Yang, Chongyin; Chen, Long; Wang, Chunsheng
Abstract : Bi@Graphite was synthesized as an ultra-fast and ultra-stable anode material for SIBs with 70% capacity retention at 300C with respect to 1C. Abstract : Sodium ion batteries (SIBs) have been revived as important alternative energy storage devices for large-scale energy storage, which requires SIBs to have a long cycling life and high power density. However, the scarcity of suitable anode materials hinders their application. Herein, we report a bismuth intercalated graphite (Bi@Graphite) anode material, which is substantially different from the previously reported metal@Graphene. In Bi@Graphite, the Bi nanoparticles between graphite interlayers enhance the capacity, while the graphite sheath provides a robust fast electronic connection for long cycling stability. The Bi@Graphite possesses a safe average storage potential of approximately 0.5 V vs. Na/Na +, delivers a capacity of ∼160 mA h g −1 at 1C (160 mA g −1 ), exhibits outstanding cycling stability ( ca. 90% capacity retention for 10 000 cycles at 20C), and can maintain 70% capacity at 300C (∼110 mA h g −1 at 48 A g −1 ), which is equivalent to full charge/discharge in 12 s. Bi@Graphite demonstrates the highest rate-capability ever reported among all anodes for SIBs. Detailed characterization results indicate that the unique Bi nanoparticle-in-graphite structure and the fast kinetics of ether co-intercalation into graphite are responsible for these significant improvements, which could translate into SIBs with excellent power densities.